1.Check that the following expressions are equivalent using the values x=-2,-1,0,1,2

12x^2-27/3 and -(-2x+3)(2x+3)

2.Prove the equivalence of the equations using algebraic manipulation

Printable View

- Nov 2nd 2008, 06:38 AMeuclid2please help solve equivalent expression question
1.Check that the following expressions are equivalent using the values x=-2,-1,0,1,2

12x^2-27/3 and -(-2x+3)(2x+3)

2.Prove the equivalence of the equations using algebraic manipulation - Nov 2nd 2008, 06:48 AMskeeter
I assume you did part 1 ... here is part 2.

$\displaystyle \frac{12x^2-27}{3} = 4x^2-9 = (2x-3)(2x+3) = -(-2x+3)(2x+3)$

btw, next time use parentheses like so ... (12x^2 - 27)/3

what you posted is ... 12x^2 - 27/3 = 12x^2 - 9